(3JMaI GdCMHGH aj fUH GdHGPGgfL hGdeMQGHs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3CYde Cf SeJ GdbHdg HeOjfI eUQ MeGgG Gddg Ydi SHYI hKdGKjf OQLg s
(3BNQgG (B:s
(3hgh GdSeJ hbS Ydi Pdc ZjQg JUH Ef TGA Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B17 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B183) s
(3JHUQI GdJQGLe(Bs
Keywords: (3Gdadcs